Stability Control of a Roadway Surrounding Rock during the Cutting and Pressure Relief of a Coal-Bearing Roof at a Shallow Mining Depth. (9th March 2022) - Tian, Chen; Liu, Yingjie; Lou, Hezhuang; Jia, Tinggui
Abstract : Recent years have seen the widespread use of a new gob-side entry retaining technology, namely, automatic roadway forming based on roof cutting and pressure relief. However, because of the complex geological conditions, stability control methods for the surrounding rock remain unexplored. In this paper, through theoretical analysis, field measurement, and numerical simulation, the stability control of a roadway surrounding rock under roof-cutting and pressure-relief conditions is studied. The key stage in the steady-state control of this type of rock is determined by establishing a mechanical model of the hard roof in the process of automatic roadway formation. The results show that the roof-cutting and pressure-relief technology outperforms the conventional mining technology in terms of surface crack development and subsidence. The roadway roof movement can be divided into three stages: a direct roof-caving activity period, a basic roof-breaking activity period, and a roof-stabilizing period. The stress above the original roadway is gradually transferred to the adjacent working face, and a stress concentration is formed on the working face 6 m away from the roadway retaining section. In this scenario, the roadway is in a stress-reducing area, which ensures its safety. Based on the research results, we suggest adding a constant resistance and large deformation anchor cable near the cutting seam side for active support. A single-hydraulic prop + I-beam + steel mesh can support the working face, and a grouting bolt support can help reinforce the broken and loose surrounding rocks at the gangue-retaining side of the roadway. Thus, the movement of the surrounding rock can be effectively controlled. An industrial test shows that the effect of retaining roadway is evidently improved.